PENGARUH SERVISCAPE TEHADAP LOYALITAS PELANGGAN TELKOMSEL: THE EFFECT OF SERVISCAPE ON TELKOMSEL CUSTOMER LOYALTY - Yenni Yuniarti; Aris Ariyanto (Konsentrasi Manajemen Pemasaran Jurusan Manajemen Fakultas Ekonomi dan Bisnis Universitas Jambi, 2018)
This study aims at examining servicescape influence on customer loyalty at GrapariTelkomsel and also examining the dominant varibel influencer. Sampleconsist of 100customers that cohosen on simple random sampling rule. While data analysis uses multiple linear regression analysis. The results showed that simultaneously ambient condition, spatial layout, signs symbol/artifacts, and employees have significant effect on customer loyalty and partially, variable spatial layout and also sign symbol/artifacts do not have a significant influence, while dominant influencer is employee. Hence it is reccomended that Grapary improve their servicecave to continually improve their service thorough employee service innovation. Keywords: ambient condition, spatial layout, signs symbol/ artifacts, employee and customer loyalty